Condições de radiação em tomografia computadorizada (TC): determinação e calibração de dosímetros - Lúcio Chagas Andrade; José Guilherme Pereira Peixoto (Brazilian Journal of Radiation Sciences, 2017)
RQT is the standard for radiation conditions in computed tomography. It simulates a beam unrelieved of a CT scanner . The camera pencil ionization dosimeter is used in CT. The LNMRI become known characterization of RQT radiation conditions and the secondary standard calibration for type pencil ionisation chambers in its lab. The obtained beam has the characteristics required by IEC 61267. The results of the calibration presented combined uncertainty expanded to 95.45% from 2.22%.